Relationship of Emotional Intelligence, Competence, Motivation and Performance of Physical Education Teachers in Elementary School Temanggung Regency - Mustofa, Arif; Rahayu, Tandiyo; Handayani, Oktia Woro Kasmini (Study Program Education and Sports, Postgraduate Universitas Negeri Semarang, 2019)
This study aims to analyze the relationship of emotional intelligence, competence, and motivation both partially and simultaneously. This research is a quantitative study using a 3x1 factor design. The population in this study were all public elementary school physical education teachers in Temanggung Regency as many as 275 people while for the sample determined using a purposive sampling technique of 85. The data analysis technique used regression correlation, assisted by SPSS. The results of the study obtained: There is a relationship between emotional intelligence and teacher performance with a value of R = 50%, There is a relationship between teacher competency and teacher performance with a value of R = 84%. There is a relationship between motivation and teacher performance with a value of R = 52%. There is a relationship between emotional intelligence and teacher competence on teacher performance with a value of R = 86%. There is a relationship between teacher competence and work motivation on performance with a value of R = 87%. There is a relationship between emotional intelligence and work motivation on teacher performance with a value of R = 67%. There is a relationship between emotional intelligence, teacher competence and motivation on teacher performance with a value of R = 89%. From the results of the data analysis, it can be concluded that emotional intelligence, competence, and motivation are related to the performance of physical education teachers in Temanggung Regency, both partially and simultaneously.